2019
DOI: 10.1111/ijd.14734
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous myoepithelioma of the foot

Abstract: 2 Kraigher O, Wohl Y, Gat A, et al. A mixed immunoblistering disorder exhibiting features of bullous pemphigoid and pemphigus foliaceus associated with Spirulina algae intake. Int J Dermato. 2008; 47: 61-63. 3 Xue X, Lv Y, Liu Q, et al. Extracellular polymeric substance from Aphanizomenon flos-aquae induces apoptosis via the mitochondrial pathway in A431 human epidermoid carcinoma cells. Exp Ther Med 2015; 10: 927-932. 4 Li B, Chu X, Gao M, et al. Apoptotic mechanism of MCF-7 breast cells in vivo and in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Tumors with similar morphologic appearances have been documented to affect acral sites previously in individual case reports or as a part of larger series, but their predilection for acral skin has not been emphasized yet 11,21–26. In addition, Antonescu and colleagues reported similar tumors as “skin and soft tissue myoepitheliomas with ductal differentiation.” They reported a marked predilection for acral skin with 8 of 13 tumors involving the hands or feet with frequent PLAG1 rearrangement, analogous to salivary gland pleomorphic adenomas 7.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with similar morphologic appearances have been documented to affect acral sites previously in individual case reports or as a part of larger series, but their predilection for acral skin has not been emphasized yet 11,21–26. In addition, Antonescu and colleagues reported similar tumors as “skin and soft tissue myoepitheliomas with ductal differentiation.” They reported a marked predilection for acral skin with 8 of 13 tumors involving the hands or feet with frequent PLAG1 rearrangement, analogous to salivary gland pleomorphic adenomas 7.…”
Section: Discussionmentioning
confidence: 99%
“…Swali et al reported a CM occurring on the medial aspect of the right foot in a 39-year old Hispanic male. The tumor showed poorly defined architecture with cells arranged in fascicles and nodules [20]. To date, only one case with a plexiform pattern has been reported [10].…”
Section: Discussionmentioning
confidence: 99%